2018
DOI: 10.3389/fcomm.2018.00026
|View full text |Cite
|
Sign up to set email alerts
|

Vocabulary Gains of Mono- and Multilingual Learners in a Linguistically Diverse Setting: Results From a German-English Intervention With Inclusion of Home Languages

Abstract: Today, group settings (e.g., in kindergarten) are more linguistically diverse than ever. However, concepts in language acquisition only rarely include this fact. This paper reports on the effects of a language intervention which is based on a concept specifically designed for linguistically diverse settings ("PROgramme for BI-and MUltilingual Children"; Festman and Rinker, 2014). The implementation of the programme and its outcomes are described with the example of a German-English-immersion kindergarten, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…This is in line with the results of Sazvar and Varmaziyar (2017), which examined the differences between Iranian EFL monolinguals and bilinguals in terms of vocabulary language learning strategies, and found that both groups were the same in terms of their proficiency, so there was no significant variation between their success in terms of vocabulary learning. Nevertheless, it is essential to underline the fact that the scores of the multilingual learners on the vocabulary achievement test were slightly higher than those of the bilingual learners in this study, similar to in earlier research (Festman, 2018;Keshavarz & Astaneh, 2010;Möhle, 1989;Arslan, 2014). This can be attributed to multilingual learners' more frequent use of vocabulary language learning strategies compared to those of bilingual learners, which had a positive impact on their learning results.…”
Section: Difference Between Bilingual and Multilingual Students' Succ...supporting
confidence: 89%
“…This is in line with the results of Sazvar and Varmaziyar (2017), which examined the differences between Iranian EFL monolinguals and bilinguals in terms of vocabulary language learning strategies, and found that both groups were the same in terms of their proficiency, so there was no significant variation between their success in terms of vocabulary learning. Nevertheless, it is essential to underline the fact that the scores of the multilingual learners on the vocabulary achievement test were slightly higher than those of the bilingual learners in this study, similar to in earlier research (Festman, 2018;Keshavarz & Astaneh, 2010;Möhle, 1989;Arslan, 2014). This can be attributed to multilingual learners' more frequent use of vocabulary language learning strategies compared to those of bilingual learners, which had a positive impact on their learning results.…”
Section: Difference Between Bilingual and Multilingual Students' Succ...supporting
confidence: 89%
“…The children first exposed to English at the bilingual school all have parents who are native speakers of Swiss German; some of the parents have had instruction in English or other FLs, but no language other than Swiss German was spoken in the home. Following Festman (2018), those I refer to as ‘international students’ (i.e., earlyPAC–int; Group 4) are children born outside of Switzerland who have grown up with another language abroad (English) that was still spoken in their international families in the new context (i.e., living and working in Switzerland). These children are in the same classes as the children in Groups 1–3.…”
Section: This Studymentioning
confidence: 99%
“…Parallel exposure to two L2s was in the focus of a lexical learning study with a group of 52 kindergarten children (mean age 3;9 years) comprised of monolingual children and those from an international background (Festman, 2018). All kindergarten children participated in a structured intervention program (combining German and English).…”
Section: Focus On the Learner: When And Why Can It Be Easier?-experiementioning
confidence: 99%